The health income hypotheses test in Taiwan - Tseng, Fu-Min (2011)
The motivation for this thesis is the investigation of the socioeconomic determinants of health in Taiwan. When considering the variations in socioeconomic status, income is an indicator much discussed in the literature because it is a complex issue and yet easily measured. Many different economists investigate income issue from the perspective of their own particular expertise. For health economists, the influence of income on health outcome is primary. Therefore, many health income hypotheses have been advanced and the debate is ongoing.